Lenalidomide in combination with intravenous rituximab (REVRI) in relapsed/refractory primary CNS lymphoma or primary intraocular lymphoma: a multicenter prospective 'proof of concept' phase II study of the French Oculo-Cerebral lymphoma (LOC) Network and the Lymphoma Study Association (LYSA). (29th January 2019) - Ghesquieres, H; Chevrier, M; Laadhari, M; Chinot, O; Choquet, S; Moluçon-Chabrot, C; Beauchesne, P; Gressin, R; Morschhauser, F; Schmitt, A; Gyan, E; Hoang-Xuan, K; et al.
Abstract: Background: Primary central nervous system lymphomas (PCNSLs) are mainly diffuse large B-cell lymphomas (DLBCLs) of the non-germinal center B-cell (non-GCB) subtype. This study aimed to determine the efficacy of rituximab plus lenalidomide (R 2 ) in DLBCL–PCNSL. Patients and methods: Patients with refractory/relapsed (R/R) DLBCL–PCNSL or primary vitreoretinal lymphoma (PVRL) were included in this prospective phase II study. The induction treatment consisted of eight 28-day cycles of R 2 (rituximab 375/m 2 i.v. D1; lenalidomide 20 mg/day, D1-21 for cycle 1; and 25 mg/day, D1-21 for the subsequent cycles); in responding patients, the induction treatment was followed by a maintenance phase comprising 12 28-day cycles of lenalidomide alone (10 mg/day, D1-21). The primary end point was the overall response rate (ORR) at the end of induction (P0 = 10%; P1 = 30%). Results: Fifty patients were included. Forty-five patients (PCNSL, N  = 34; PVRL, N  = 11) were assessable for response. The ORR at the end of induction was 35.6% (95% CI 21.9–51.2) in assessable patients and 32.0% (95% CI 21.9–51.2) in the intent-to-treat analysis, including 13 complete responses (CR)/unconfirmed CR (uCR; 29%) and 3 partial responses (PR; 7%). The best responses were 18 CR/uCR (40%) and 12 PR (27%) during the induction phase. The maintenance phase was started and completed by 18 and 5 patients, respectively. With a median follow-up of 19.2 months (range 1.5–31), the median progression-free survival (PFS) and overall survival (OS) were 7.8 months (95% CI 3.9–11.3) and 17.7 months (95% CI 12.9 to not reached), respectively. No unexpected toxicity was observed. The peripheral baseline CD4/CD8 ratio impacted PFS [median PFS = 9.5 months (95% CI, 8.1–14.8] for CD4/CD8 ≥ 1.6; median PFS = 2.8 months, [95% CI, 1.1–7.8) for CD4/CD8 < 1.6, P  =   0.03). Conclusions: The R 2 regimen showed significant activity in R/R PCNSL and PVRL patients. These results support assessments of the efficacy of R 2 combined with methotrexate-based chemotherapy as a first-line treatment of PCNSL. Clinical trials number: NCT01956695.